Модифіковані графеноподібні плівки як новий клас напівпровідників зі змінною шириною забороненої зони - Lytovchenko, V.G.; Strikha, M.V.; Klyui, M.I. (Publishing house "Academperiodika", 2022)
It has been theoretically predicted and experimentally proved that the deformation of thin graphite-like carbon films is accompanied by the appearance of an energy gap at the $K$-point, the gap being proportional to a strain. A metal–semiconductor phase transition in a thin graphite (or multilayered graphene) film has been revealed. This phenomenon can be promising for the development of semiconducting materials.